Impact of cognitive reserve on clinical and neuropsychological measures in patients with mild cognitive impairment. (August 2020) - Haussmann, Robert; von Lieres und Wilkau, Amrei F E; Sauer, Cathrin; Nilles, Fabienne; Donix, Markus
Objective: Cognitive reserve influences age of onset, speed of progression, and clinical manifestations of Alzheimer's disease. We investigated whether cognitive reserve interacts with clinical and neuropsychological parameters in mild cognitive impairment (MCI). Methods: In this cross-sectional study, we recruited 273 people (70.6 ± 10.1 years, 54.6% women) suffering from subjective memory complaints ( n = 65), MCI ( n = 121), or dementia ( n = 87). Patients underwent neuropsychological evaluation, laboratory testing, and brain imaging. Additionally, we obtained information on years of education and help-seeking motivation. Results: MCI patients with a university degree were significantly older than those without (71.6 ± 9.6 vs. 66.9 ± 10.3, p = 0.02). University-educated MCI patients demonstrated superior performance in verbal fluency. Intrinsic help-seeking motivation (self-referral) was associated with higher cognitive reserve. Female MCI patients presented with greater intrinsic motivation. Conclusion: Cognitive reserve modulates clinical and neuropsychological measures in patients with MCI.